1996
DOI: 10.1007/s004110050034
|View full text |Cite
|
Sign up to set email alerts
|

Association of fallout radiocesium with soil constituents: effect of sterilization of forest soils by fumigation with chloroform

Abstract: The effect of soil sterilization by chloroform fumigation on the release of fallout radiocesium incorporated in the fungal biomass of the organic layer of two forest soils was investigated by applying a sequential extraction procedure for radiocesium. The amount of the biomass in all soil samples was estimated by determination of the dissolved organic carbon (DOC) before and after fumigation, and qualitatively also by the ergosterol test. The five fractions obtained by sequential extraction (modified Tessier p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The latter solid species are more resistant in the soil. Compared to results of relatively short-term deposition (Baumann et al, 1996;Rigol et al, 1999), our soils showing long-term deposition had lower amounts of 137 Cs bound to exchangeable, microbial biomass or organic matter fractions but higher amounts as persistent and residual fractions, which might be due to the well-known ''aging effect'' (Absalom et al, 1996;Spezzano, 2005). Recent study of soils affected by the Chernobyl accident indicate that most of the 137 Cs is in the residual fraction (Hou et al, 2003), which supports this aging phenomenon.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The latter solid species are more resistant in the soil. Compared to results of relatively short-term deposition (Baumann et al, 1996;Rigol et al, 1999), our soils showing long-term deposition had lower amounts of 137 Cs bound to exchangeable, microbial biomass or organic matter fractions but higher amounts as persistent and residual fractions, which might be due to the well-known ''aging effect'' (Absalom et al, 1996;Spezzano, 2005). Recent study of soils affected by the Chernobyl accident indicate that most of the 137 Cs is in the residual fraction (Hou et al, 2003), which supports this aging phenomenon.…”
Section: Resultssupporting
confidence: 64%
“…Several studies have reported the upward movement of 137 Cs in forest soil, where fungal activities play key role in translocation of 137 Cs (Brückmann and Wolters, 1994;Rafferty et al, 1997). Being aware of the importance of the availability of 137 Cs retained by fungi, some investigators tried to determine the fraction of nuclear fallout 137 Cs in fungal hyphae in soil (Brückmann and Wolters, 1994;Baumann et al, 1996). Recent study indicates that a critical part of fungal mycelia and fruit bodies of mycorrhizal fungi are water soluble (Vinichuk et al, 2005), which contributes to the mobility of 137 Cs in the forest soils.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in plutonium and americium speciation with depth have been studied in grassland soil (Bunzl et al, 1995b) and of plutonium and caesium in forest soil . The effect of soil sterilisation on 137 Cs partitioning was also investigated and found to be soil dependent (Baumann et al, 1996). A four-stage sequential extraction has been used to partition Chernobyl-derived 137 Cs in a coniferous forest soil in Sweden (Fawaris and Johanson, 1995).…”
Section: Radionuclidesmentioning
confidence: 99%